2018
DOI: 10.1097/md.0000000000011481
|View full text |Cite
|
Sign up to set email alerts
|

Altered long noncoding RNAs and survival outcomes in ovarian cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
2
9
0
Order By: Relevance
“…Recent research has documented the biological role of lncRNAs in OC [7][8][9], and several studies have demonstrated an association between lncRNA expression and patient survival in this cancer [11,12]. There are currently between 32 and 58 lncRNAs that have been reported to have a role in OC pathogenesis [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has documented the biological role of lncRNAs in OC [7][8][9], and several studies have demonstrated an association between lncRNA expression and patient survival in this cancer [11,12]. There are currently between 32 and 58 lncRNAs that have been reported to have a role in OC pathogenesis [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis has indicated that aberrant expression of lncRNAs is positively correlated with poor survival outcomes in OC. During this study, 11 lncRNAs, including NEAT1, HOTAIR, MALAT1, TC010441, ANRIL, AB073614, CCAT2, ZFAS1, UCA1, SPRY4-IT1, and HOXA11as, were significantly associated with reduced overall survival, progression-free survival, and disease-free survival in OC patients [ 188 ]. Similarly, Luo et al revealed that upregulation of eight lncRNAs; HOTAIR, NEAT1, CCAT2, UCA1, C17orf91, ANRIL, TC0101441, and AB073614 and downregulation of 5 lncRNAs; ASAP1-IT1, AC104699.1.1, LINC00472, FAM215, and RP11-284N8.3.1 were correlated with poor prognosis in OC given a probability for harnessing these lncRNAs as potential prognostic biomarkers for OC [ 189 ].…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkersmentioning
confidence: 99%
“…Promisingly, the prognostic value of lncRNAs in ovarian cancer has been documented, which are mostly up-regulated. 16 In the An initial conclusion was comprehended as that LINC00176 was highly expressed in ovarian cancer tissues and cells featured with strengthened cell capabilities of proliferation, migration, invasion and EMT along with weakened apoptotic property. Hitherto, limited studies have enclosed the role of LINC00176 in malignancy.…”
Section: Linc00176 Regulates Cp Expression Via Promotion Of the Intmentioning
confidence: 99%